2021
DOI: 10.35445/alishlah.v13i1.386
|View full text |Cite
|
Sign up to set email alerts
|

Tungku Tigo Sajarangan, Tali Tigo Sapilin: A Strategy Towards World Class University Based on Local Wisdom Perspective

Abstract: This study aims to analyze and describe Tungku Tigo Sajarangan, Tali Tigo Sapilin as an indicator to achieve a world-class university. Descriptive qualitative research methods were used to answer this objective by conducting several procedures such as interviews with the cultural expert of Minangkabau, interviews with the educational experts, direct observation of learning activities in the university, and study the scientific literature. Thematic content analysis was used to find informative descriptions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Kualifikasi utama, selain pendidikan, untuk dianggap sebagai Cadiak Pandai adalah partisipasi aktif dalam pemerintahan nagari. Jadi aman untuk mengatakan bahwa setiap orang di pemerintahan nagari merupakan bagian dari Cadiak Pandai (Amri et al, 2021). Posisi Cadiak Pandai memiliki kesamaan dengan Niniak Mamak dan Alim Ulama, di mana mereka merupakan lembaga yang disegani di Indonesia.…”
Section: Penyelenggaraan Sistem Pemerintahan Nagariunclassified
“…Kualifikasi utama, selain pendidikan, untuk dianggap sebagai Cadiak Pandai adalah partisipasi aktif dalam pemerintahan nagari. Jadi aman untuk mengatakan bahwa setiap orang di pemerintahan nagari merupakan bagian dari Cadiak Pandai (Amri et al, 2021). Posisi Cadiak Pandai memiliki kesamaan dengan Niniak Mamak dan Alim Ulama, di mana mereka merupakan lembaga yang disegani di Indonesia.…”
Section: Penyelenggaraan Sistem Pemerintahan Nagariunclassified
“…In Minangkabau it is known as the "tigo sapilin rope, tigo sajarangan furnace,". Tungku Tigo Sajarangan is an integral Hasan Basri, Mahyudin Ritonga, Mursal Mursal / The Role of Tungku Tigo Sajarangan in Educating Adolescent Morality through the Indigenous Values of Sumbang Duo Baleh part of the leadership of Niniak Mamak (traditional leaders), Alim Ulama (religion), and Cadiak Pandai (scientists/intellectuals) (Amri et al, 2021). The local wisdom of Tungku Tigo Sajarangan functionally plays a role in shaping the patterns and behavior of the community (Mursal & Cahya, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies that have relevance to this research, Amri and his colleagues conducted research related to local wisdom as the basis for realizing world-class education, from the results of their analysis it was concluded that the mindset of Minangkabau community leaders could be used as an alternative in building a classy university world (Amri et al, 2021). Azzahra et al (Azzahra et al, 2021) conducted a study on the concept of Islamic education and gender equality, from the results of their analysis it was found that Minangkabau culture has governed the concept of gender equality, and this has complete relevance to the concept of education Islam.…”
Section: Introductionmentioning
confidence: 99%
“…Identity of local culture, social beliefs and traditional values are strongly affected by modern trends surrounding consumerism and homogenisation (Purnama et al, 2021). Local wisdom in a country like Indonesia is fading lately, with some even no longer has practitioners, left out altogether in the name of modernisation, a change of mindset and increasing living needs, making the people put aside (either willingly or left with no choice) the values and meanings of traditional legacies and wisdoms (Amri et al, 2021). This needs to change if we want to preserve local wisdom legacies in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…The grand idea in doing this sort of preservation is to form an institution above this issue that is unanimous in its creation to later study, develop and maintain local wisdoms in Indonesia (Amri et al, 2021). Learning with ways of local wisdom means learning close to daily life, especially social lives of the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%